Panel: Peculiarities in Human Factors Consulting on Government Projects. (September 2016) - Horst, Dick; Fitzpatrick, Sean; Panzer, Rich; Lebson, Cory; Pass, Jeff
This panel will provide a forum for ruminating about the unique challenges that arise for human factors consultants when working on government projects. Even practitioners who are well-experienced in the private, non-profit, or academic sectors, frequently encounter obstacles when offering their services to government agencies. Government contracting involves its own set of terminology, business practices, and procurement procedures. We have assembled a panel of well-experienced human factors engineering consultants to identify and discuss such peculiarities They each have considerable recent experience in federal government IT projects as well as a history that includes project work in other business sectors. Drawing upon that experience we will ask them to discuss what makes government consulting different. The audience will have ample opportunities to pose questions to the panelists about the challenges faced in government human factors and user experience consulting work and how they have dealt with those challenges.